Does Management of Working Capital Affects Profitability: Evidence from Manufacturing Sector of Pakistan - Noman, Muhammad; Ahmed, Waseem; Saghir, Ahsen; Khan, Naeem (iRASD Journal of Economics, 2023)
This paper examines the effect of management of working capital on profitability of manufacturing companies of Pakistan. The paper employed annual data ranging from 2014 to 2021 of 23 manufacturing companies of Pakistan. The dynamic generalized method of moments (GMM) technique is applied to see the aforementioned relationship. Findings of the study are that cash conversion cycle and all its elements except receivable days are positively and significantly associated with profitability (ROA) while CCC is negatively and significantly associated with profitability (ROE). Further, a more comprehensive research is recommended based on comparison between developing and developed nations in context of working capital practices.